2019
DOI: 10.15244/pjoes/95182
|View full text |Cite
|
Sign up to set email alerts
|

A Rural Household Heating Method that Combines a Regenerative Electric Boiler with PV Power Generation

Abstract: The heating mode of a regenerative electric boiler in China's rural area includes many problems such as the increase of heating cost, the high expense of government subsidies and tr investment cost, etc. Consequently, this paper proposes a new heating method that combines a regenerative electric boiler with distributed photo-voltaic power generation. The photovoltaic software PVsyst was used to simulate generating capacity, and a system-wide economic efficiency calculation model was established. Taking a famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…By integrating a photovoltaic-electric boiler heating system, Chen et al ( 2022b ) achieved a 58.9% cost saving in life cycle specific ambient heating costs ($2.77/kWh). To replace bulk coal and achieve clean rural domestic heating, Zhang and Gao ( 2019 ) combined distributed photovoltaic with a thermal storage electric boiler to generate electricity for rural heating in Beijing. They found that rooftop photovoltaic heat generation can meet the requirements of the electric thermal storage boiler, saving 3.596 tons of greenhouse gas emissions per year and $825.477 in environmental management costs.…”
Section: Green Solutions For Home Heatingmentioning
confidence: 99%
“…By integrating a photovoltaic-electric boiler heating system, Chen et al ( 2022b ) achieved a 58.9% cost saving in life cycle specific ambient heating costs ($2.77/kWh). To replace bulk coal and achieve clean rural domestic heating, Zhang and Gao ( 2019 ) combined distributed photovoltaic with a thermal storage electric boiler to generate electricity for rural heating in Beijing. They found that rooftop photovoltaic heat generation can meet the requirements of the electric thermal storage boiler, saving 3.596 tons of greenhouse gas emissions per year and $825.477 in environmental management costs.…”
Section: Green Solutions For Home Heatingmentioning
confidence: 99%
“…In order to solve the problem of replacing electricity with coal in rural areas of the Beijing, Tianjin and Hebei region in China, individuals used distributed photovoltaic power generation to alleviate this problem, and analyzed a typical case of a family in a rural area. Through economic benefits analysis, it is found that this method not only reduces the cost of heating, but also produces good environmental benefits [19].…”
mentioning
confidence: 99%